2021
DOI: 10.18400/tekderg.651399
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection for Implementation of the Mechanistic-Empirical Pavement Design Guide (MEPDG) in Izmir, Turkey

Abstract: Developing countries like Turkey are trying to implement the Mechanistic-Empirical Pavement Design Guide (MEPDG). The implementation of this method requires comprehensive local data collection, evaluation, and, if necessary, a local calibration. The objective of this study is to prepare local data such as climate, traffic, and materials for evaluation and local calibration of MEPDG for Izmir City. For this purpose, the climate and traffic data were obtained, analysed, and converted to the MEPDG format. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…During simulation experiments, set α = 0.15 and β = 4. According to China's Code for design of urban road engineering [63] and the situation of the city, set k (1) , k (2) , k (3) = (1, 1.5, 1.5) and N (1) , N (2) , N (3) = (1.5, 30,20).…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…During simulation experiments, set α = 0.15 and β = 4. According to China's Code for design of urban road engineering [63] and the situation of the city, set k (1) , k (2) , k (3) = (1, 1.5, 1.5) and N (1) , N (2) , N (3) = (1.5, 30,20).…”
Section: Results Analysismentioning
confidence: 99%
“…Therefore, researchers and city officials have been very interested in studying road maintenance as a significant aspect of urban infrastructure. To meet the optimal structural rehabilitation design and future budget needs, a technical evaluation of the traffic network's quality based on a pavement management system (PMS) is required [28][29][30][31]. Traffic networks include not only road sections but also intersections.…”
Section: Smart Mobilitymentioning
confidence: 99%
“…Climatic inputs are essential to predict the temperature and moisture profiles in the pavement over the design life. Pavement layer temperature and moisture predictions are calculated on an hourly basis and used to estimate the material properties for the foundation and pavement layers throughout the design life [15,27]. It was shown that seasonal temperature variations carry out a considerable drop in pavement durability and significantly affect the overall performance of the pavement system, which is greatly affected by temperature and moisture [8,28].…”
Section: Climate Effect In the M-e Methodsmentioning
confidence: 99%
“…There are limited number of studies in Turkey on the M-E design. In the Izmir (city in Turkey) study [15], the focus was the data collection to implement the M-E design, but no runs were performed. In the only study performing the M-E based rigid pavement designs [16], 8 cities were studied individually by simply matching them with the selected US city/weather stations.…”
Section: Determination Of Climatic Regions For the M-e Pavement Design In Turkeymentioning
confidence: 99%
See 1 more Smart Citation